2014
DOI: 10.4155/ppa.14.15
|View full text |Cite
|
Sign up to set email alerts
|

Formulation Strategies to Improve Oral Peptide Delivery

Abstract: Delivery of peptides by the oral route greatly appeals due to commercial, patient convenience and scientific arguments. While there are over 60 injectable peptides marketed worldwide, and many more in development, most delivery strategies do not yet adequately overcome the barriers to oral delivery. Peptides are sensitive to chemical and enzymatic degradation in the intestine, and are poorly permeable across the intestinal epithelium due to sub-optimal physicochemical properties. A successful oral peptide deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 170 publications
(139 reference statements)
1
38
0
2
Order By: Relevance
“…and low values (1)(2)(3)(4)(5)(6)(7)(8)(9)(10) [165]. The hydrophobic moiety of the surfactant also influences enhancement action.…”
Section: Hlb In Permeation Enhancementmentioning
confidence: 99%
See 1 more Smart Citation
“…and low values (1)(2)(3)(4)(5)(6)(7)(8)(9)(10) [165]. The hydrophobic moiety of the surfactant also influences enhancement action.…”
Section: Hlb In Permeation Enhancementmentioning
confidence: 99%
“…The capacity of C 10 to clinically improve intestinal drug absorption was demonstrated in rectal suppositories of ampicillin, for which it gained approval in Sweden (1992) and Japan (1985 [2]). C 10 is efficacious in both small and large intestine, although it was more effective in the colon for FD4 and insulin in rat intestinal instillation [20,70,118,184,185].…”
Section: Case 1: C 10mentioning
confidence: 99%
“…Medium chain fatty acids (MCFA) are powerful permeation enhancers acting in part by re-organising tricellulin and claudin 5 proteins at the tight junction (18), as well as through a mild detergent fluidizing effect on the plasma membrane (19). Several peptides are in oral clinical trials using MCFA-based technologies (20,21). One of the lead MCFA in clinical trials, capric acid, is found in mM concentrations in dairy products, and its sodium salt (C 10 ) has shown extensive enhancement effects in vitro and in vivo (22).…”
Section: Introductionmentioning
confidence: 99%
“…Peptides, including insulin, are unstable and poorly permeate the small intestinal epithelium, hence their low oral bioavailability [38]. PEs are present in several solid-dose oral formulations for peptides, of which two technologies are advanced clinically [39,40].…”
Section: Hca: Cytotoxicity Of Polymers and Permeation Enhancersmentioning
confidence: 99%